2015
DOI: 10.1186/s12871-015-0102-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of palonosetron, granisetron, and ramosetron for the prevention of postoperative nausea and vomiting after laparoscopic gynecologic surgery: a prospective randomized trial

Abstract: BackgroundSelective 5-hydroxytryptamine type 3 (5-HT3) receptor antagonists are reported to have potent antiemetic effects for postoperative nausea and vomiting (PONV). The purpose of this study was to prospectively evaluate the efficacy of palonosetron, granisetron, and ramosetron for the prevention of PONV in patients undergoing laparoscopic gynecologic surgery.MethodsIn this prospective, randomized observational study, 105 healthy female patients who were undergoing laparocopic hystectomy under general anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 21 publications
(26 reference statements)
2
30
0
Order By: Relevance
“…The 5-HT 3 antagonists (palonosetron and ramosetron) were administrated during the early phase of the operation in four studies [14–16,19] and at the end of the surgery in four [17,18,20,21]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5-HT 3 antagonists (palonosetron and ramosetron) were administrated during the early phase of the operation in four studies [14–16,19] and at the end of the surgery in four [17,18,20,21]. …”
Section: Resultsmentioning
confidence: 99%
“…Six studies [14–16,1820] compared the effectiveness of palonosetron to that of ramosetron in the prevention of early PON. Five studies [15,16,1820] compared late PON, and six studies [14–16,1820] compared the effectiveness of the drugs on overall PON.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were similar to study conducted by Lee WS et al, who found that there were no significant differences in the overall incidence of postoperative nausea and vomiting and complete responders for Palonosetron, Granisetron and Ramosetron group. [25] The percentage of patients who had nausea between 4-12 hours of the study period was 20.00% with Granisetron, 13.33% with Ramosetron and 6.67% with Palonosetron. Similarly, the percentage of patients who had nausea between 12-24 hours of the study period was 16.67% with Granisetron, 10.00% with Ramosetron and 6.67% with Palonosetron.…”
Section: Discussionmentioning
confidence: 87%
“…15 In a comparative study of antiemetics for the prevention of postoperative nausea and vomiting after laparoscopic gynaecologic surgery, the number of complete responders at 48 h after the surgery was maximum for ramosetron, though the differences between the groups were not statistically significant. 16 In all the three groups, the complete response rates in the acute phase were seen to be better as compared to the respective complete response rates in the delayed phase in the terms of proportions. In a phase II trial of ramosetron and dexamethasone in the prevention of cisplatin-induced nausea and vomiting, the prevention of acute emesis seemed to be more effective than the prevention of delayed emesis.…”
Section: Figure 3 Comparative Effect Of the Study Drugs In Controllimentioning
confidence: 94%